FAKTOR MELATARBELAKANGI LANSIA MEMILIH TINGGAL DI PANTI JOMPO DARUSSA’ADAH LHOKSEUMAWE, ACEH - Iskandar, Iskandar; Iqbal, Muhammad; Rahayu, Maulita (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Elderly who choose to live in nursing homes because the children of the elderly already have their own families so that the elderly are sometimes alone at home alone or do not have partners anymore because they have died, therefore the elderly need more care and attention in nursing homes. The purpose of the study was to determine the factors behind the elderly choosing to live in the Darussa'adah Nursing Home in Gampong Cot Girek, Lhokseumawe City. The research design is descriptive correlation with a population of 36 respondents and a sample of 36 respondents using total sampling. This research was conducted on 09 to 12 July 2021. The results showed that there was a relationship between family factors (P = 0.007), socialization factors (P = 0.001), family problems (P = 0.001), factors no one paid attention to (P = 0.001) P = 0.018), the factor does not want to bother the family (P = 0.014), the self-experience reflection factor (P = 0.005), and the economic factor (P = 0.006) with the elderly choosing to live in the Darussa'adah Nursing Home in Gampong Cot Girek, Lhokseumawe City. 2021. It is recommended for the orphanage to invite elderly families to make regular family visits once a week so that the elderly do not feel alone and lonely.